Denotation and application mechanism of complicated network shared management information model - GAO Zhi-peng; QIU Xue-song; WANG Zhi-li; LI Wen-jing (Tongxin xuebao)
With IP-based environment of complicated network, in order to solve the network management’s problem of system expansibility, multi-domain management, uniform resource description, the method for modeling and using the shared management information model was presented from the mechanism of denotation to application. First, improve the language OWL, and OWL-NM was presented to build the template of shared management information model. Then, the rule aggregation mapping the IDL-based model to OWL-NM-based model was given. The third, storage application mechanism that can store the shared management information model to database was shown. At last, a prototype system was designed to prove the conclusions.